Global Trading of Carbon Emissions and India. - Kalpagam, U. (2009)
This paper examines keys features of the global carbon market. It first highlights the infrastructure for global trading of carbon credits, and then examines the functioning of the regulated market segment covered by the Kyoto Protocol. The voluntary segment of the carbon market though small is a growing one, but it has its own problems as well. Notwithstanding the ethical and perhaps also economic arguments often raised against adopting market-based solutions rather than direct limitations through quantitative restrictions and penal taxes on polluting parties, it is argued that the carbon market affords opportunities to India in contribution to reduction of Green House Gases (GHGs) by adopting environmentally sustainable development practices, and in reaping gains from trading in environment related financial instruments.